Small Group Discussion in Actual ELT Speaking Classes - Luli Sari Yustina; Besral Besral; Syayid Sandi Sukandi (Masyarakat Linguistik Indonesia Universitas Andalas, 2021)
Finding out aspects of learning in small group discussions that matched with the Indonesian Higher Order Thinking Skills (HOTS) and aspects of local cultures that contradict small group discussion excellence is the purpose of this research. The method of this research is qualitative. Researchers use document analysis by collecting documents from various sources such as journals and articles, which are following the research that the researcher will do. The results of this research show that the implementation of HOTS instruction in teaching speaking skills investigated from students' small group discussions will be advantageous and beneficial. In essence, HOTS instructions give a positive effect on students speaking skills significantly.